Kepraktisan Modul Elektronik Menggunakan Aplikasi Sigil Berorientasi Pendekatan Saintifik Materi Perubahan Lingkungan Kelas X Jenjang Sekolah Menengah Atas - Jannah, Jannah; Kaspul, Kaspul; Utami, Nurul Hidayati (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Electronic modules are electronic teaching materials that are arranged systematically, covering competencies that will be mastered by students and equipped with an attractive appearance. Sigil is an e-book maker application with a product format in the form of epub. This study aims to describe the validity and practicality of the Electronic Module Using Sigil Application Oriented the Scientific Approach to Environmental Change Materials for Class X High School Level. The study is part of Research and Development which refers to the 4-D model, which consists of 4 main stages, Define, Design, Develop and Disseminate. The subjects in this study were 9 students of class X SMAN 7 Banjarmasin. The instrument used is a student response questionnaire. The results of the practicality test obtained an average percentage of 88.54% (very practical) with a percentage of 88.00% in the display aspect (very good), 92.44% in the material presentation aspect (very good) and 85.18% in the benefits aspect (very good), overall it is categorized as very practical and can be used by students.Keywords - Electronic module, Sigil application, Scientific approach, Environmental change